Physiological responses to on-court vs running interval training in competitive tennis players - Fernandez -Fernandez, J.; Sanz-Rivas, D.; Sanchez-Munoz, C.; Gonzalez de la Aleja Tellez, J.; Buchheit, M.; Mendez-Villanueva, A. (Journal of Sports Science & Medicine, 2011)
The aim of this study was to compare heart rate (HR), blood lactate (LA) and rate of perceived exertion (RPE) responses to a tennis-specific interval training (i.e., on-court) session with that of a matched-on-time running interval training (i.e., off-court). Eight well-trained, male (n = 4) and female (n = 4) tennis players (mean ± SD; age: 16.4 ± 1.8 years) underwent an incremental test where peak treadmill speed, maximum HR (HRmax) and maximum oxygen uptake (VO2max) were determined. The two interval training protocols (i.e., off- court and on-court) consisted of 4 sets of 120 s of work, interspersed with 90 s rest. Percentage of HRmax (95.9 ± 2.4 vs. 96.1 ± 2.2%; p = 0.79), LA (6.9 ± 2.5 vs. 6.2 ± 2.4 mmol·L-1; p = 0.14) and RPE (16.7 ± 2.1 vs. 16.3 ± 1.8; p = 0.50) responses were similar for off-court and on-court, respectively. The two interval training protocols used in the present study have equivalent physiological responses. Longitudinal studies are still warranted but tennis-specific interval training sessions could represent a time-efficient alternative to off-court (running) interval training for the optimization of the specific cardiorespiratory fitness in tennis players.